1998
DOI: 10.1038/25374
|View full text |Cite
|
Sign up to set email alerts
|

Changes in thymic function with age and during the treatment of HIV infection

Abstract: The thymus represents the major site of the production and generation of T cells expressing alphabeta-type T-cell antigen receptors. Age-related involution may affect the ability of the thymus to reconstitute T cells expressing CD4 cell-surface antigens that are lost during HIV infection; this effect has been seen after chemotherapy and bone-marrow transplantation. Adult HIV-infected patients treated with highly active antiretroviral therapy (HAART) show a progressive increase in their number of naive CD4-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

97
1,482
15
29

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,721 publications
(1,640 citation statements)
references
References 27 publications
97
1,482
15
29
Order By: Relevance
“…New tools have been recently developed to better assess thymus function. Using a molecular marker of recent thymic emigrants, a DNA circle from the T-cell rearrangement process named TREC [8], an increase in naïve T-cells carrying this circle after HAART has been described [9]. Another approximation to assess the thymus role in HIV-1 infected patients would be the evaluation of thymic volume by computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…New tools have been recently developed to better assess thymus function. Using a molecular marker of recent thymic emigrants, a DNA circle from the T-cell rearrangement process named TREC [8], an increase in naïve T-cells carrying this circle after HAART has been described [9]. Another approximation to assess the thymus role in HIV-1 infected patients would be the evaluation of thymic volume by computed tomography (CT).…”
Section: Introductionmentioning
confidence: 99%
“…Thymic epithelial space, which is the best biological correlate of functionally active tissues, declines from about 7 cm 3 in the young adult to about 1 cm 3 in the 55 to 65 year old. Recent studies have shown islands of functional tissue in the thymus of the elderly (Haynes et al, 2000;Steinmann et al, 1985;Steinmann, 1986); however, it is uncertain whether production of new thymocytes in these residual tissues is of quantitative importance.In the absence of phenotypic markers specific for thymic emigrants, most studies of thymic output have relied on measuring T-cell receptor excision circles (TREC) (Douek et al, 1998;Kong et al, 1999). These signal-joint TRECs are formed during T-cell receptor (TCR)-α-chain rearrangement, when a substantial portion of the TCR δ locus is excised.…”
mentioning
confidence: 99%
“…Even naïve T cells are, therefore, present in identical replicates generated during and shortly after T-cell development in the thymus or in the periphery. Estimates of clonal sizes have come from the dilution of TRECs during thymic development (Douek et al, 1998;Okamoto et al, 2002). We have used TREC measurements in cord blood of babies born at different gestational ages (Schonland et al, 2003).…”
mentioning
confidence: 99%
“…The reduction in the cell number of the thymic microenvironment over the years is a genetically pre-programmed and well-controlled physiological process, 22 and is reflected in the slow-down of T-cell export observed in normal individuals already in the first years of life. 23 Thus, it can be speculated that PRSS16 has a function in thymic development. The only splice variant of PRSS16 that was constitutively expressed in nearly all samples, independently of the age of the donor, is PRSS16-4.…”
Section: Discussionmentioning
confidence: 99%